Quo Vadis Ekonomi Indonesia Pasca Covid-19 - Harris Turino Kurniawan; Adhi Setyo Santoso (JAAF (Journal of Applied Accounting and Finance), 2020)
CNN Indonesia, on 24 July 2020, reported that "BI predicted Indonesia to enter recession gap in the third quarter of 2020". Several online media immediately grabbed with the more bombastic article entitled, "Indonesia's economy is on the brink destruction." In the 2/2020 quarter, the conditions got worse. Singapore is a country the earliest reported 2/2020 quarter growth of - 41.2%, lowest throughout the history of the country's founding. Its annual growth becomes- 12.6% (yoy). Singapore's economy, which is supported by international trade and infrastructure, is under severe pressure. Malaysia hasn't reported its economic growth but is forecast to experience contraction amounted to 9.7%. Indonesia itself is also predicted to enter negative growth in 2/2020 quarter of - 3.8%. The question is whether the Indonesian economy is so bad? Indonesia's economic quo Vadis?